Reviewing Youth Development Principles As Applied to the 4-H Youth Development Program - Joy C. Jordan; Marilyn Norman (EDIS, 2006)
Because 4-H is the youth development arm of Land Grant University outreach, 4-H youth development professionals are responsible for knowing and applying to their programs the most current and valid information regarding support for the growth and development of the youth in their communities. This document is 4HS FS101.4, one of a series of the 4-H Youth Development Department, UF/IFAS Extension. Published May 2006.